PENGEMBANGAN MEDIA SCRAPBOOK DENGAN DESAIN “KATA TANYA” UNTUK MELATIH KEMAMPUAN MEMBACA LANJUTAN PESERTA DIDIK DI KELAS IV SEKOLAH DASAR - Setiana Putri; Odien Rosidin; Rina Yuliana (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This research aims to develop a Scrapbook learning media product with a "question word" design to train advanced reading skills in Theme 2 Subtheme 1 Learning 1 class IV elementary school material. The place of research was carried out at Sentul 4 Serang State Elementary School. The subjects of this development research is grade IV. The research model used is the Research & Development model which has been modified with 6 steps, i.e, analyzing potential and problems, collecting data, designing product designs, validating product designs, revising product designs, and product trials (limited trials). Researchers collected data using preliminary study techniques, interviews, observation, questionnaire collection and documentation. This scrapbook media has passed the validation stage by six experts by getting an overall score of 86.6 in the very worthy category. The overall score was obtained from an average accumulation of 84% for media experts, 84% for language experts and 92% for material experts with a very decent category from the three expert assessments. The trial was carried out on class IV students by collecting questionnaires and getting a satisfaction score of 97.8% in the very good category. It can be concluded that the development of scrapbook media with a "question word" design to train advanced reading skills is declared feasible for development and use by fourth grade elementary school students.